The Effectiveness of Guided Inquiry and INSTAD towards Students’ Critical Thinking Skills on Circulatory System Materials - Putra, B. K. B.; Prayitno, B. A.; Maridi, M. (Jurnal Pendidikan IPA Indonesia, 2018)
Critical Thinking Skills (CTSs) are fundamental skills possessed by students to adapt to the external challenges of 21st-century. To empower students’ CTSs, Guided Inquiry and INSTAD may work effectively. This research aimed to see the effectiveness of guided inquiry and INSTAD toward students’ critical thinking skills. This research was a quasi-experimental. The instrument to get the CTSs data was a valid essay test according to Facione. The sampling technique employed was the intact group sampling method. The number of participants involved was 188 XI grade science program students of SMAN 7 Surakarta; a middle-quality school. The total number of research sample was 64; 32 students in the Guided Inquiry class and the other 32 students in the INSTAD class. Hypothetical test using ANCOVA resulted in a 5% of significance level. The results indicated that there were significant differences of CTSs on circulatory system topic between the INSTAD and Guided Inquiry class. The students who experience the INSTAD class has higher CTSs than those joined the Guided-Inquiry class.